The incidence detection of tuberculosis in patients with infertility and abnormal uterine bleed: a study in North Indian population - Kaur, Simmanjit; Santpur, Unmesh; Mor, Sunita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Tuberculosis (TB) remains a major global health problem, responsible for ill health among millions of people each year. TB ranks as the second leading cause of death from an infectious disease worldwide, after the human immunodeficiency virus (HIV). The latest estimates included in this report are that there were 9.0 million new TB cases in 2013 and 1.5 million TB deaths (1.1 million among HIV-negative people and 0.4 million among HIV-positive people). In India the incidence of genital tuberculosis is nearly about 18%. And in female genital tract it is estimated that 18% in India suffer from genital TB. Methods: The study was carried-out during November 2014 to March 2016 at Maharishi Markandeshwar deemed to be University, MMIMSR Mullana (Ambala). A total of 100 females of reproductive age attending the Gynaecology Outpatient were finally recruited on the basis of inclusion and exclusion criteria. Results: In our study majority i.e. 39 (39.0%) patient were found in the group of 20-29 years of age followed by 38 (38.0%) patients in the group of 30-39 years of age. Only 23 (23.0%) were found in the group of 40-49 years of age. In our study majority i.e. 54 (54.0%) patients were from Haryana followed by 44 (44.0%) patients were from Uttar Pradesh and only 2 (2.0%) patients were from Punjab. Out of 100 patients majority i.e. 76 (76.0%) patients had negative TB with either of investigation and only 24 (24.0%) patients had positive TB with either of investigation. Conclusions: Female genital tuberculosis affects the females of reproductive age group. The disease manifests itself as pelvic inflammatory disease in its acute form with menstrual irregularities and later infertility, and is almost always secondary to a primary lesion elsewhere.